FlowForge: A Prototype for Generating User Stories and Gherkin Test Cases from BPMN with DMN Integration and Pattern Matching - Riskiana, Rosa Reska; Ryan Oktaviandi Susilo Wibowo; Arpriansah Yonathan (School of Computing, Telkom University, 2024)
Business Process Model and Notation (BPMN) is a powerful tool for modeling complex business workflows, but its potential for automation in testing remains underexplored. Manual testing of BPMN models is time-intensive and error-prone, necessitating automated approaches to generate test cases directly from the models. This paper presents FlowForge, a tool that transforms BPMN models into User Stories and Gherkin test cases, leveraging Decision Model and Notation (DMN) to enhance test completeness. By addressing challenges related to complex pathways, exception handling, and evolving process structures, FlowForge bridges gaps in existing prototypes, enabling automated test case generation with 100% path coverage within BPMN models. The study demonstrates the successful mapping of BPMN elements to detailed Gherkin syntax while identifying limitations, such as incomplete cross-pool verification and restricted pattern libraries. These findings highlight the tool's potential for improving the efficiency and reliability of BPMN-based testing and offer insights for future development to expand its applicability to more diverse business processes.